A proposal on the classification of systems tracts: application to the allostratigraphy and sequence stratigraphy of the cretaceous colombian basin. part 2: barremian to maastrichtian (2002)
The Barremian to Maastrichtian interval of the sedimentary succession from the Cretaceous Colombian Basin is divided in stratigraphic sequences and in several allostratigraphic units, which include the Fómeque, Une, and Chipaque Alloformations, the Guadalupe Allogroup, and the lower part of the Guaduas Alloformation. The division is based on the recognition of regional surfaces of sedimentological discontinuity, corresponding mainly to Transgressive Surfaces (TS) located at the base of Transgressive Systems Tracts (TST), and Regressive Surfaces (RS) coincident with Sequence Boundaries (SB) and located at the base of Regressive Systems Tracts (RST). The proposed allostratigraphic units are composed of facies belts, which extend across the whole basin and include laterally adjacent and essentially synchronous lithostratigraphic units. The base of the Fómeque Alloformation is located en the Transgressive Surface (TS) at the Hauterivian/Barremian boundary. The base of the Une Alloformation is located on the Regressive Surface (RS) at the Aptian/Albian boundary. The base of the Chipaque Alloformation on the Transgressive Surface (TS) at the Cenomanian /Turonian boundary, and the base of the Guadalupe Allogroup on the Regressive Surface (RS) at the Santonian/Campanian boundary. The Une Alloformation is subdivided in allomembers, using the Transgressive Surface (TS) at the Lower Albian! Middle Albian boundary and the Regressive Surface (RS) at the Albian/Cenomanian boundary. In the same way, the Guadalupe Allogroup is subdivided in the Lower, Middle, and Upper Guadalupe Alloformations, using the Transgressive Surface (TS) at the Lower Campanian/Upper Campanian boundary and the Regressive Surface (RS) at the Campanian! Maastrichtian boundary. The succession is capped by the lower part of the Guaduas Alloformation, which is located over the Transgressive Surface (TS) at the Lower Maastrichtian/Upper Maastrichtian boundary.